A New Dialogue in Ballet Pedagogy: Improving Learner Self-Sufficiency Through Reflective Methodology. Issue 2 (3rd April 2018) - Weidmann, Chelsea
ABSTRACT : Current research into reflective pedagogy in dance almost exclusively discusses the tertiary education population. Additionally, the research is primarily focused on concert modern dance and creative dance pedagogies, techniques, and choreography. Ballet technique programs in precollegiate populations have, so far, been left out of the conversation. This article aims to open that dialogue, beginning with an examination and clarification of John Dewey's philosophy. Strategies for implementing reflective teaching techniques are modeled for beginning, intermediate, and advanced ballet classes. The goal is to demonstrate that reflective pedagogy can, and should, be included throughout the training process because it (1) will enhance the results of sound, tradition-based teaching; and (2) can be applied to pretertiary students in a formal ballet program without diluting the already established decorum, culture, and pedagogical lineage.